Estructuración del proceso de compras y optimización del modelo de inventarios para la empresa Pintuger Gaitán (2020)
The present undergraduate project aims to structure the purchasing process and optimize the inventory model for the company PINTUGER GAITAN, developing an appropriate system and proposing an improvement in administration, preparing manuals of functions and procedures of greater relevance in the proposed areas. To gather the information, research methods were used, and diagnostic tools were used to identify the problems; and in this way, to know in a more detailed way the internal state of the organization. Subsequently, flow and process diagrams were made for the purchasing and inventory areas, following the sequence of each operation and identifying their respective functions. The manager's approval was obtained to access the purchase history of the last 39 months, the information was tabulated, and a classification of the products was made through the ABC system, the information was classified by categories, a sample was obtained and the model of maximums and minimums combined with the stochastic model was applied. Finally, manuals of functions and key procedures were prepared, for the organization to control the contracting processes, establishing a guide and orientation for the organization's personnel.